Diagnostic Challenges and Imaging Considerations for Intraparotid Facial Nerve Schwannoma: A Case Report and Literature Review - Luzha, Jeton; Kopp, Markus; Wiesmüller, Marco; Taha, Lava; Rupp, Robin; Mantsopoulos, Konstantinos; Koch, Michael; Iro, Heinrich; Sievert, Matti (American Journal of Case Reports, 2024)
Background: A mass in the parotid gland usually indicates parotid gland neoplasia. Warthin tumors or pleomorphic adenomas are common differential diagnoses. Less frequently, other differential diagnoses and sites of origin are considered. Schwannomas are rare, benign tumors in the head and neck region. Even more rarely, these tumors occur in the intraparotid course of the facial nerve. In the following, we report about 2 patients in whom a mass in the right parotid gland was found incidentally during magnetic resonance imaging (MRI). Case Reports: We reviewed data from the literature on intraparotid facial nerve schwannomas (IPFNS) and compared them with those from our cases. The focus was on data such as clinical history, clinical symptoms, electroneurography, and various imaging modalities, such as ultrasonography and MRI combined with diffusion-weighted imaging. Conclusions: It is challenging to distinguish facial nerve schwannomas from other neoplasms. Patient’s history, clinical symptoms, MRI examination with diffusion-weighted imaging, and high-resolution ultrasound imaging are decisive factors for diagnosis and should be performed when IPFNS is suspected. Diagnosis and therapy for IPFNS remain challenging. A wait-and-scan approach could be an option for patients with small tumors and good facial nerve function. On the other hand, patients with advanced tumors associated with limited facial nerve function can benefit from surgical approaches or stereotactic radiosurgery.
CRIS-Team Scopus Importer:2024-04-12
Keywords: Facial Nerve Diseases; Facial Paralysis; Nerve Sheath Neoplasms; Parotid Gland